Ω3‐polyunsaturated fatty acids suppress lipoprotein‐associated phospholipase A2 expression in macrophages and animal models. Issue 9 (18th June 2015) - Li, Zhuang; Ren, Wenzhi; Han, Xiaolei; Liu, Xingxing; Wang, Gangqi; Zhang, Mingjun; Pang, Daxin; Ouyang, Hongsheng; Tang, Xiaochun
<x xml:space="preserve">Abstract</x> Scope ω3‐polyunsaturated fatty acids (ω3‐PUFAs) have beneficial effects on cardiovascular function, and lipoprotein‐associated phospholipase A2 (Lp‐PLA2) is associated with the risk of cardiovascular disease. Here, we investigated the effects of ω3‐PUFAs on Lp‐PLA2 expression in vitro and in vivo and explored the mechanisms involved. Methods and results Human monocyticcells (THP‐1) were induced into macrophages in an in vitro model. ω3‐PUFAs suppressed Lp‐PLA2 expression; the suppression induced by docosahexaenoic acid (DHA) was related to reduced inflammation. Tumor necrosis factor‐α (TNF‐α) was employed to stimulate the phosphorylation of p38 mitogen‐activated protein kinase (MAPK), nuclear factor‐κB (NF‐κB) p65 and Lp‐PLA2 expression in macrophages. The stimulation was inhibited by DHA and the anti‐inflammatory drug sodium salicylate. Moreover, the stimulation of Lp‐PLA2 expression by TNF‐α could be suppressed by NF‐κB and MAPK pathway inhibitors. Then, chronic inflammation was induced in an in vivo mouse model, resulting in an increase in Lp‐PLA2 expression in peripheral blood mononuclear cells (PBMCs) and arteries. This increase was suppressed by ω3‐PUFAs. Inhibition of Lp‐PLA2 transcription in PBMCs was also observed in ω3‐PUFA‐enriched swine. Conclusion Our results demonstrate that the protective effects of ω3‐PUFAs against cardiovascular events may be related to the suppression of Lp‐PLA2 levels.